A tango by two superpowers: China-US cooperation in trilateral aid and implications for their bilateral relations. Issue 2 (4th May 2018) - Zhang, Denghua
ABSTRACT: The US-China relationship continues to be characterized by both competition and cooperation in recent years. Cooperation in the development sector is one little-known new aspect of such cooperation. This paper therefore examines why and how the two superpowers have undertaken cooperation in trilateral aid projects, and implications for bilateral relations. By tracing China-US policy engagement on development cooperation and examining their most recent trilateral aid project in the Asia-Pacific region, the paper argues that the US aims to use trilateral aid cooperation to engage with China and shape it into a responsible stakeholder, while China uses trilateral cooperation to build a cooperative image and facilitate the broad China-US relationship.